Analysis of Community Forest Utilization by Livestock Farmers 0f HKm Ulusena Farmers Group in Ulusena Village, Moramo District, South Konawe Regency - Muhammad Babul Rachman; Siti Azizah; Dede Aprylasari (Journal of Agriprecision & Social Impact, 2026)
This study aims to analyze the utilization of Community Forestry, the role of farmers group, and the perceptions of livestock farmers who are members of “HKm Ulusena” Farmers Group regarding the utilization of the Ulusena Community Forest. This study was conducted from November 2024 to July 2025 in Ulusena Village, Moramo District, South Konawe Regency, Southeast Sulawesi Province. This study was conducted using a qualitative approach. The determination of informants was carried out using a non-probability sampling method with purposive sampling and snowball sampling techniques. Data sources in this study used primary and secondary data. Data collection was obtained through observation, interviews, and documentation. The data analysis process used the Miles and Huberman method, namely data reduction, data presentation, and drawing conclusions. The utilization of the Ulusena Community Forest is divided into three categories: land use, utilization and collection of non-timber forest products (NTFPs), and utilization of environmental services. Livestock serves as a secondary source of income for livestock farmers, members of the Ulusena Community Forest Farmer Group. Utilization in livestock involves the use of forest areas as land for growing green fodder. “HKm Ulusena” Farmers Group has not been actively operating, so a new group management structure was formed. The new management structure periodically carries out a process of increasing the capacity of regional, institutional, and business management to foster group synergy by reactivating group activities. Farmers' perceptions of the use of the Ulusena Community Forest tend to be positive. Positive impacts of the Ulusena Community Forest utilization include obtaining permits for non-timber forest product (NTFP) management, obtaining economic resources from NTFPs, and obtaining resources to support the livestock sector.